Psychometric properties of the Arabic Perceived Digital Well-Being Scale (PDWS) in Saudi young adults - Emadeldin M. Elsokkary (PLoS ONE, 2026)
Rapid digital transformation in Saudi Arabia has intensified young adults’ day-to-day reliance on smartphones, increasing the need for balanced, culturally appropriate measures of perceived digital well-being. This study aimed to psychometrically validate the Arabic version of the Perceived Digital Well-Being Scale (PDWS) among Saudi young adults aged (18–25). A cross-sectional instrument-validation study was conducted with (N = 450) participants. The full sample was randomly split into two independent analytic subsamples: Sample (1) for exploratory factor analysis (EFA) (n = 225) and Sample (2) for confirmatory factor analysis (CFA) (n = 225); convergent validity was examined in both subsamples. EFA supported a clear three-factor structure (Emotional, Social, Cognitive). CFA confirmed a second-order model with excellent fit: χ²(116)=133.275, p = .130, χ²/df=(1.149), CFI=(.986), TLI=(.983), RMSEA=(.026), and SRMR=(.055). Convergent validity was supported by positive associations with life satisfaction (SWLS) and negative associations with fear of missing out (FoMO), with the same pattern observed across both subsamples (Sample (2): SWLS r=(.416–.550), p < .01; FoMO r=(−.321–-.254), p < .01). Internal consistency was acceptable across subsamples (Cronbach’s α=(.759–.886); McDonald’s ω=(.761–.889)). Overall, the Arabic PDWS demonstrates strong initial evidence of structural validity, theoretically consistent convergent validity, and adequate reliability, supporting its use as a multidimensional measure of perceived smartphone-related digital well-being among Saudi emerging adults.